KEMAMPUAN NUMERIK SISWA SEKOLAH MENENGAH ATAS DALAM PEMECAHAN MASALAH MATEMATIS - Umi Nur Haafidah; Hamdani Hamdani; Dian Ahmad BS (Jurnal AlphaEuclidEdu, 2022)
The importance of problem solving skills is based on the results of the Trends in International Mathematics and Science Study (TIMSS) survey which means that students' mathematical problem solving abilities in Indonesia are still in a very low category. Where one factor in the low problem solving ability of students is the low numerical ability of students. Based on these results, researchers are interested in revealing deeper results regarding students' numerical abilities in solving mathematical problems. Thus, this study was conducted with the aim of knowing students' numerical abilities in solving mathematical problems. The method used in this research is descriptive method. With the form of descriptive quantitative research, the subjects in this study were students of class XII MIA MA Khulafaur Rasyidin and the object of this research was numerical ability in solving mathematical problems. The data collection technique used a test technique with the data analysis technique used, namely the average percentage. The results of data analysis showed that the numerical ability of students in solving mathematical problems was included in the medium category with the percentage obtained at 58.428%. Which means that overall there are still students who are not fast and careful in doing arithmetic calculations when solving problem solving problems properly.